Del Palacio Negro a la Selva Lacandona Louis Althusser en México - Ortega Reyna, Jaime (Ariadna Ediciones, 2023)
This book reviews the implications that the work of the French philosopher Louis Althusser had in Mexico, in the journey from the late 1960s to the collapse of Marxist discourses in public life. Unlike other works, some intellectual receptions hitherto little addressed are exposed, such as those of the philosophy of science.